INTEGRASI NILAI-NILAI BUDAYA LOKAL DALAM PENDIDIKAN AGAMA ISLAM - M.Yusuf M.Yusuf; Abdul Hadi (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
The integration of local cultural values into Islamic Religious Education (IRE) is a strategic effort to bridge Islamic teachings with the socio-cultural context of the student community. This article aims to examine the concept, urgency, and model of integrating local cultural values into IRE, while identifying the challenges and opportunities for its implementation in educational institutions. The method used is a literature study by analysing various scientific sources in the form of books, journal articles, and educational policy documents. The results of the study show that the integration of local culture in PAI can strengthen the internalisation of Islamic values, increase the relevance of learning, and build the character of students who are religious and rooted in local wisdom. However, this integration requires caution so as not to conflict with the principles of Islamic creed and sharia. Therefore, a clear conceptual and pedagogical framework is needed so that integration can run harmoniously and effectively.